Urban transit network design problems: a review of population-based metaheuristics - Tarajo, Buba Ahmed; Lee, Lai Soon (Universiti Putra Malaysia Press, 2016)
The urban transit network design problem (UTNDP) involves the development of a transit route set and associated schedules for an urban public transit system. The design of efficient public transit systems is widely considered as a viable option for the economic, social, and physical structure of an urban setting. This paper reviews four well-known population-based metaheuristics that have been employed and deemed potentially viable for tackling the UTNDP. The aim is to give a thorough review of the algorithms and identify the gaps for future research directions.